The roles of long noncoding RNAs in the regulation of OCT4 expression - Rui-Ting Zhou; Yi-Ran Ni; Fan-Jun Zeng (Stem Cell Research & Therapy, 2022)
Abstract OCT4 is a major transcription factor that maintains the pluripotency of stem cells, including embryonic stem cells, induced pluripotent stem cells and cancer stem cells. An increasing number of long noncoding RNAs have been reported to participate in the regulation of OCT4 expression through various mechanisms, including binding with the OCT4 gene promoter to regulate local methylation; promoting chromosomal spatial folding to form an inner ring, thereby aggregating OCT4 cis-acting elements scattered in discontinuous sites of the chromosome; competitively binding microRNAs with OCT4 to upregulate OCT4 expression at the posttranscriptional level; and sharing a promoter with OCT4. Moreover, the transcription of some long noncoding RNAs is regulated by OCT4, and certain long noncoding RNAs form feedback regulatory loops with OCT4. In this review, we summarized the research progress of the long noncoding RNAs involved in the regulation of OCT4 expression.